Some Chemistry Indices of Clique-Inserted Graph of a Strongly Regular Graph - Chun-Li Kan; Ying-Ying Tan; Jia-Bao Liu; Bao-Hua Xing (Complexity)
In this paper, we give the relation between the spectrum of strongly regular graph and its clique-inserted graph. The Laplacian spectrum and the signless Laplacian spectrum of clique-inserted graph of strongly regular graph are calculated. We also give formulae expressing the energy, Kirchoff index, and the number of spanning trees of clique-inserted graph of a strongly regular graph. And, clique-inserted graph of the triangular graph Tt, which is a strongly regular graph, is enumerated.